Managing potentially radioactive scrap metal recommendations of the National Council on Radiation Protection and Measurements. (National Council on Radiation Protection and Measurements, 2002)
Annotation This report identifies the sources, inventories, and characteristics of potentially radioactive scrap metal, outlines management considerations concerning its handling, discusses the development of release standards, and offers its own recommendations. Specific consideration is given to issues of radiation protection and protection against orphan source contamination. Appendices examine metal-making technology and the detection and surveillance of radiation. A glossary defines key terms and lists relevant acronyms and abbreviations. Annotation copyrighted by Book News, Inc., Portland, OR.
"Issued November 19, 2002."
Keywords: Radioactive substances -- Safety measures.; Radioactive wastes -- Management.; Radioactive waste disposal.; Radiation -- Safety measures.; Environmental management.; Environmental health.; elektronické knihy; electronic books